(untitled) (Bangladesh Journal of Botany, 2020)
To study the effect of new generation herbicides on soil enzyme L-asparaginase a field experiment was designed and carried out on maize as test crop. The weed management practices tested were two preemergence herbicides (pendimethalin and atrazine @ 1.0 kg a.i/ha each) and two post-emergence herbicides topramezone @ 25.2 g a.i/ha at 15 DAS,and tembotrione @ 105 g a.i/ha at 15 DAS and combine application of pre- and post emergent herbicides topramezone + atrazine @ 25.2 + 250 g a.i/ha at 15 DAS, tembotrione + atrazine @ 105 + 250 g a.i/ha was applied at 15 DAS and in addition to these the unweeded control and hand weeding (twice at 20 and 40 days) treatments. Soil samples were collected at 15 days intervals and enzyme activity was assayed. In pre-emergence herbicides, control, and hand weeding, there was an increase in the activity of the enzyme from 0 to 60 days and then decrease till harvest, whereas in post emergence herbicide both stimulation and inhibition were observed.